2001
DOI: 10.1103/physrevb.64.224509
|View full text |Cite
|
Sign up to set email alerts
|

Detailed electronic structure studies on superconductingMgB2and related compounds

Abstract: Our recent electronic structure studies on series of transition metal diborides indicated that the electron phonon coupling constant is much smaller in these materials than in superconducting intermetallics. However experimental studies recently show an exceptionally large superconducting transition temperature of 40 K in MgB 2 . In order to understand the unexpected superconducting behavior of this compound we have made electronic structure calculations for MgB 2 and closely related systems. Our calculated De… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
92
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(107 citation statements)
references
References 51 publications
13
92
0
2
Order By: Relevance
“…20 (Fig.5) on the base of the full-potential LAPW method, 32 and computed the corresponding dielectric function ǫ IB 1 (ω) by the KK transformation. The plasma frequencies reported by different groups 30,31,32 are also close to each other. We used the values ω p,aσ = 4.14 eV, ω p,aπ = 5.89 eV, ω p,cσ = 0.68 eV and ω p,cπ = 6.85 eV.…”
Section: B Comparison With Ab Initio Calculationssupporting
confidence: 77%
“…20 (Fig.5) on the base of the full-potential LAPW method, 32 and computed the corresponding dielectric function ǫ IB 1 (ω) by the KK transformation. The plasma frequencies reported by different groups 30,31,32 are also close to each other. We used the values ω p,aσ = 4.14 eV, ω p,aπ = 5.89 eV, ω p,cσ = 0.68 eV and ω p,cπ = 6.85 eV.…”
Section: B Comparison With Ab Initio Calculationssupporting
confidence: 77%
“…The topmost valence band is separated from the bottom-most conduction band by an indirect band gap of 2.5 eV. It is apparent from the occurrence of the gap that the material is an insulator which is in agreement with earlier studies of Ravindran et al 11 and Harima. 12 The 2px and 2py orbitals of B and C mainly contribute to the density of states at the top of the valence band, whereas Mg provides very little contribution to the total DOS at this energy.…”
Section: Resultssupporting
confidence: 80%
“…Similar to graphite, MgB 2 with different B-B in-plane and inter-plane distances should exhibit a strong anisotropy in the thermal, mechanic and electronic properties. Electronic structure calculations have showed that the inter-plane, Mg-B bonding, could be considered small as compared to the main contribution to chemical bond that has σ-character derived from the B:p x +p y electrons (this was also found by P. Ravindran et al 11 ). The in-plane boron bonds are covalent, while the inter-plane Mg-B bond is strongly ionic.…”
Section: Introductionmentioning
confidence: 70%